PERANCANGAN TATA LETAK FASILITAS PABRIK COCO FIBER DAN COCOPEAT MENGGUNAKAN METODE SYSTEMATIC LAYOUT PLANNING DAN ALGORITMA BLOCPLAN - Efendi, Anna Gustika; Ihsan Hamdy, Muhammad; Surayya Lubis, Fitriani; Isnaini , Muhammad; Nazaruddin, Nazaruddin (JURNAL PERANGKAT LUNAK, 2023)
Meranti Islands is one of the coconut producing areas in Indonesia. Based on BPS data in 2021, coconut production in the area is around 29.26 tons. The high production of coconut has made the local government plan to build a small and medium industrial center to process the coconut. A small and medium industrial center that will be built requires a layout design for cocofiber and cocopeat factories. This study aims to provide the best proposed layout for the factory. The methods used are Systematic Layout Planning (SLP) and Blocplan Algorithm. The resulting 3 alternative layouts of SLP method and 20 alternative layouts of blocplan algorithm are then selected to determine the most efficient alternative layout based on the smallest material handling cost. The results showed that the alternative layout of the SLP method results had a smaller inter-departmental distance than the blocplan alternative layout, which was around 89.51 m with a total material handling distance of 326.58 m for cocofiber and cocopeat products. This research shows that designing the layout of cocofiber and cocopeat factory facilities is more effective using the SLP method than Blocplan, because SLP considers more supporting factors.